A Novel Cognitive Radio enabled IoT System for Smart Irrigation (Journal of Informatics and Mathematical Sciences, 2017)
A novel architecture is proposed and analyzed that incorporates cognitive radio concept into Internet of Things (IoT) for smart irrigation system. The proposed system will optimize the use of natural resource i.e. water. Typically, the flow of water for irrigation of crop fields is not uniform due to many reasons including non-uniform terrain, availability of resources at different sites and etc.This un-even flow produces lesser product from the farms. The proposed system uses two data types to model the different conditions of crop filed. Based on these assumptions, the proposed system is analyzed. The simulation results for the proposed scenario are also presented.
Keywords: Smart irrigation; IoT; Cognitive radio